2022
DOI: 10.18632/aging.204435
|View full text |Cite
|
Sign up to set email alerts
|

Single nuclei profiling identifies cell specific markers of skeletal muscle aging, frailty, and senescence

Abstract: Aging is accompanied by a loss of muscle mass and function, termed sarcopenia, which causes numerous morbidities and economic burdens in human populations. Mechanisms implicated in age-related sarcopenia or frailty include inflammation, muscle stem cell depletion, mitochondrial dysfunction, and loss of motor neurons, but whether there are key drivers of sarcopenia are not yet known. To gain deeper insights into age-related muscle loss, we performed transcriptome profiling on lower limb muscle biopsies from 72 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 97 publications
6
48
0
Order By: Relevance
“…Our data indicates MYH6 (alpha isoform in cardiac muscle), MYH4 (primarily in rodent limb muscles) and MYH14 (a non-muscle myosin) were significantly different between Leiden groups, however the abundance of each of these isoforms was <1% of the total MYH content. This is in line with the current literature, which shows MYH6 and MYH4 to be completely absent or in very low abundance in human skeletal muscle fibers 1,7,30 . Nevertheless, the mean iBAQ-calculated quantity of MYH6 in our data was 5e-4 in Leiden group 1 and 8e-6 in Leiden group 0, which led to it being significantly different between groups despite the low amount.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our data indicates MYH6 (alpha isoform in cardiac muscle), MYH4 (primarily in rodent limb muscles) and MYH14 (a non-muscle myosin) were significantly different between Leiden groups, however the abundance of each of these isoforms was <1% of the total MYH content. This is in line with the current literature, which shows MYH6 and MYH4 to be completely absent or in very low abundance in human skeletal muscle fibers 1,7,30 . Nevertheless, the mean iBAQ-calculated quantity of MYH6 in our data was 5e-4 in Leiden group 1 and 8e-6 in Leiden group 0, which led to it being significantly different between groups despite the low amount.…”
Section: Discussionsupporting
confidence: 93%
“…We found that MYH protein quantities calculated using iBAQ from DIA-NN precursor data with subsequent actin normalization were more reliable in assigning MYH isoforms based on established knowledge of MYH subtype distributions within human skm compared to protein quantities from MaxLFQ. We characterized the differences in type 1 and 2A fiber types based on the quantities of the regulatory and structural proteins (troponins, tropomyosins, MYL proteins, Z-line linking proteins, and a sarcoplasmic reticulum protein) and found a majority of the proteins ( Figure 2 and Figure 5) to also be congruent with previous findings 3,30 . For example, MYL3, which we found to be significantly higher in Leiden 1 (mostly type 1 fibers), has been previously reported as 10 times more abundant in type 1 versus type 2A fibers 3 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Few articles have applied snRNAseq to skeletal muscle (Zeng et al, 2016;Dos Santos et al, 2020;Jiang et al, 2020;Kim et al, 2020;Petrany et al, 2020;Orchard et al, 2021;Eraslan et al, 2022). Of these, three groups isolated nuclei directly from mouse muscle (Dos Santos et al, 2020;Kim et al, 2020;Petrany et al, 2020), two used cell cultures (Zeng et al, 2016;Jiang et al, 2020), and four used human skeletal muscle (Orchard et al, 2021;Eraslan et al, 2022;Perez et al, 2022;Scripture-Adams et al, 2022), although Orchard and colleagues focussed on analyzing accessible chromatin regions by means of ATAC-seq. To isolate nuclei directly from muscle, these reports used fiber dissection and dounce homogenization (Dos Santos et al, 2020;Scripture-Adams et al, 2022), or a mix of various homogenization methods and detergents (Petrany et al, 2020;Orchard et al, 2021;Eraslan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…To isolate nuclei directly from muscle, these reports used fiber dissection and dounce homogenization (Dos Santos et al, 2020;Scripture-Adams et al, 2022), or a mix of various homogenization methods and detergents (Petrany et al, 2020;Orchard et al, 2021;Eraslan et al, 2022). One recently published work used fresh muscle samples with a proprietary instrument specifically designed for sc/snRNAseq (S2 Genomics) (Perez et al, 2022).…”
Section: Introductionmentioning
confidence: 99%